EFFECT OF STRATEGIC MANAGEMENT PRACTICES ON ORGANIZATIOAL PERFORMANCE IN TELECOM COMPANIES IN SOMALIA - Sigane, Ali Mohamud; GICHINGA, DR. LUCY GICHINGA (IJRDO - Journal of Applied Management Science, 2018)
The general objective of this study was to investigate the effects of strategic management practices on organizational performance in companies in Mogadishu. Specifically, this study was investigated the effects of strategic resource management, organizational innovation, core competency and quality management practices on telecom   companies in Mogadishu. Strategic management practices decisions rank among the most critical types of managerial decisions made in a company and can have major long-term implications, both positive and negative. Telecom companies were only succeeding if their strategic management practices decisions are made well.  In order to ensure the importance of strategic management practices decisions for telecom companies and its effects on organizational performance play the effectiveness and efficiency in telecom companies. The objective of this study is to investigate the effect of strategic management practices on organizational performance and the specific objectives of this study are strategic resource management, organizational innovation, core competency and quality management practices. The sampling procedure of this study is used non-probability sampling procedure particularly purposive sampling or judgmental sampling. The sample size of this study is 50 and was selected from the target population 100 by using Solven’s formula. This research was employed quantitative data collection method whereby data was gathered by the use of closed ended questionnaires which are self-administered. The data collected was analyzed using the software called Statistical Package for the Social Sciences (SPSS) version 20 and results was shown in terms of frequency distribution and percentages. A regression model was applied to determine the relationship between strategic resource management, organizational innovation, core competency and quality management practices as the independent variables and organizational performance for telecom companies as the dependent variable. The results reveal that strategic resource management, organizational innovation, core competency and quality management practices have significant and positive effects on organizational performance in telecom companies in Mogadishu.  Based on the findings of this study, the following conclusions were drawn. The results reveal that strategic resource management, organizational innovation, core competency and quality management practices have significant and positive effects on organizational performance in the selected telecom companies in Mogadishu Somalia. Multiple regression analysis was conducted for hypotheses testing.  The study recommended that to become market leaders, top managers of telecom companies in Mogadishu should exploit its core competences and to develop technical innovation that generate competitive advantage to enhance of the organization.